The urban fringe of Indian cities : Professor Jaymala Diddee felicitation volume - Dikshit, Jutta K. (Jaipur : Rawat Publications, 2011)
Papers presented at a seminar.
Includes bibliographical references and index.
Keywords: Cities and towns -- India -- Growth -- Congresses; Land use, Urban -- India -- Congresses; City planning -- India -- Congresses